ELECTROCHEMICAL EVALUATION OF HUMIDITY BASED PROTON CONDUCTIVITY OF ALUMINIUM(III) TARTRATE - Bhuvaneswari, G.; Rameshkumar , S. (International Journal of Membrane Science and Technology, 2023)
Aluminium(III) tartrate was synthesized by simple solution crystallization and its humidity dependent proton conductivity was evaluated using electrochemical impedance spectroscopy. The compound exhibited very low DC conductivity and AC conductivity in the as synthesized form and dried conditions. However, upon exposing to 100% relative humidity(RH) the AC conductivity of the compound increased significantly with time and is several orders greater than DC conductivity. The structural stability of the compound was analysed by FTIR and PXRD experiments. The compound has good structural stability on hydration, dehydration and rehydration. The proton conductivity of the sample decreased several orders on dehydration and it bounces back to original value on rehydration. The complex exhibited reversible proton conductivity with respect to moisture. The variation of proton conductivity with temperature implies that the compound exhibits Grotthuss type proton conductivity.